Converging Effects of Three Different Endocrine Disrupters on Sox and Pou Gene Expression in Developing Rat Hippocampus: Possible Role of microRNA in Sex Differences - Lichtensteiger, Walter; Bassetti-Gaille, Catherine; Rehrauer, Hubert; Georgijevic, Jelena Kühn; Tresguerres, Jesus A.F.; Schlumpf, Margret (Frontiers in Genetics, 2021)
Endocrine disrupting chemicals (EDCs) can impair hippocampus-dependent behaviors in rat offspring and in children. In search for key processes underlying this effect, we compared the transcriptomes of rat hippocampus on postnatal day 6 after gestational and lactational exposure to three different EDCs at doses known to impair development of learning and memory. Aroclor 1254, a commercial PCB mixture (5 mg/kg or 0.5 mg/kg), or bisphenol A (5 mg/kg or 0.5 mg/kg) were administered in chow, chlorpyrifos (3 mg/kg or 1 mg/kg) was injected subcutaneously. Male hippocampus exhibited a common effect of all three chemicals on genes involved in cell-autonomous processes, Sox6, Sox11, Pou2f2/Oct2, and Pou3f2/Brn2, all upregulated at the high dose. Additional genes of the Sox and Pou families were affected by only one or two of the chemicals. Real time RT PCR showed a comparable expression change for bisphenol A also at the lower dose. Female hippocampus exhibited much fewer genes with expression changes (almost none with false discovery rate <0.05), and none of the genes of the Sox and Pou families was affected. Since gene network analyses in male hippocampus suggested a link between Sox6 and miR-24, known to be repressed by activation of ER-alpha and to repress Sox6 in other tissues, this microRNA was measured. miR-24 was downregulated by all chemicals at the high dose in males. Values of Sox6 mRNA and miR-24 were inversely correlated in individual male hippocampus samples, supporting the hypothesis that the change in Sox6 expression resulted from an action of miR-24. In contrast, miR-24 levels remained unchanged in hippocampus of females. A sexually dimorphic response of miR-24 may thus be at the basis of the sex difference in Sox6 expression changes following exposure to the three chemicals. ER-alpha expression was also sex-dependent, but the expression changes did not parallel those of potential downstream genes such as Sox6. Sox6 is known to suppress differentiation of Parvalbumin (Pvalb)-expressing interneurons. Individual Sox6 levels (FPKM) were inversely correlated with levels of Pvalb, but not with markers of Sox6-independent interneuron subpopulations, Nos1 and 5HT3aR. Effects on interneuron development are further suggested, in males, by expression changes of Nrg1 and its receptor Erbb4, controlling interneuron migration. Our study disclosed new types of EDC-responsive morphogenetic genes, and illustrated the potential relevance of microRNAs in sexually dimorphic EDC actions.